Dynamical evidence for a strong tidal interaction between the Milky Way and its satellite, Leo V. Issue 1 (12th January 2017) - Collins, Michelle L. M.; Tollerud, Erik J.; Sand, David J.; Bonaca, Ana; Willman, Beth; Strader, Jay
Abstract: We present a chemodynamical analysis of the Leo V dwarf galaxy, based on the Keck II DEIMOS spectra of eight member stars. We find a systemic velocity for the system of $\langle v_r\rangle = 170.9^{+ 2.1}_{-1.9}{\rm \, km\, s^{-1}}$ and barely resolve a velocity dispersion for the system, with $σ _{vr} = 2.3^{+3.2}_{-1.6}{\rm \, km\, s^{-1}}$, consistent with previous studies of Leo V. The poorly resolved dispersion means we are unable to adequately constrain the dark-matter content of Leo V. We find an average metallicity for the dwarf of [Fe/H] =−2.48 ± 0.21 and measure a significant spread in the iron abundance of its member stars, with −3.1 ≤ [Fe/H] ≤−1.9 dex, which clearly identifies Leo V as a dwarf galaxy that has been able to self-enrich its stellar population through extended star formation. Owing to the tentative photometric evidence for the tidal substructure around Leo V, we also investigate whether there is any evidence for tidal stripping or shocking of the system within its dynamics. We measure a significant velocity gradient across the system, of $\frac{{\rm d}v}{{\rm d}χ } = -4.1^{+2.8}_{-2.6}{\rm \, km\, s^{-1}}$ arcmin −1 (or $\frac{{\rm d}v}{{\rm d}χ } = -71.9^{+50.8}_{-45.6}{\rm \, km\, s^{-1}}$ kpc −1 ), which points almost directly towards the Galactic Centre. We argue that Leo V is likely a dwarf on the brink of dissolution, having just barely survived a past encounter with the centre of the Milky Way.